UNFORESEEN OBJECTS IDENTIFICATION IN ÃâÃâFTZÃâÃâ FIELD BASED ON GROUND-PENETRATING RADAR (GPR) DATA - CHRISTIAN DANIEL HASOLOAN SIAGIAN NIM: 12314015, FRITZ
Preliminary study of construction site ground is compulsory before a construction starts. The studyÃ‚Â’s goal is to make sure that all the ground that will be used for construction is clear from debris that will obstruct the project. One of several geophysical method that can map quickly and efficiently these unforeseen utility debris is the ground-penetrating radar method. Other than speed and accuracy, this method is highly favored in preliminary construction preparations because it is a non-destructive survey method. This method uses electromagnetic waves that is emitted to the ground and recaptures the signal that is splitting because of electrical and magnetic property contrast of the materials below the ground, which are conductivity (σ), dielectric constant (ε), and magnetic permitivity (μ). The purpose of this research Research is done in FTZ field which is located in Balikpapan, East Borneo. The survey design used is as follows: a set of Zond12e GPR control unit coupled with a 300MHz shielded antenna, sampling frequency of 1800MHz, and the number of samples taken is set to 512. After data acquisition is done, forward modeling is commenced by making a model which refers to the data collected from the field, then inputing the electrical properties depending on what object that is suspected to be the cause of the wave splitting. Next, forward modeling and acquisition result is analysed and compared to one another. The end result of this research is the mapping of unforeseen utilities that are found in the research area.